Zn-doped Sb70Se30 thin films with multiple phase transition for high storage density and low power consumption phase change memory applications. (15th March 2020) - Liu, Ruirui; Hu, Anya; Zhao, Zihan; Zhou, Haitao; Zhai, Jiwei; Zhou, Xiao; Song, Sannian; Song, Zhitang
Abstract: The single layer Zn44 Sb39 Se17 thin film, being fabricated by Sb70 Se30 and Zn using co-sputtering method, exhibits double phase change transition. The double phase change processes are mainly attributed to the crystallization of the Sb and ZnSb phases. The potential operating temperature for ten years of two phase change processes are 64 °C and 179 °C, of which the good stability of the second phase change can be sufficient for the autoelectronic applications. Meanwhile we also discovered the Zn44 Sb39 Se17 thin film presents apparent low power consumption in comparison with Ge2 Sb2 Te5 and other reported Sb-Se based phase change materials. Graphical abstract: Image, graphical abstract